Simultaneous determination of three antituberculosis drugs in the serum of patients with spinal tuberculosis by capillary electrophoresis. Issue 37 (2nd September 2021) - Wu, Xuehua; Che, Xiaoming; Qiu, Zhixue; Chao, Jingyuan; Kong, Zhanping; Li, Haili
Abstract : Capillary electrophoresis is a simple, rapid, and sensitive method for measuring PZA (1), INH (2), and RFP (3) simultaneously in serum samples of patients with spinal tuberculosis. Abstract : The pharmacokinetic variations of a single drug in an antituberculosis regimen are associated with acquired drug resistance and therapy failure. This study aimed to develop a simple and effective method for monitoring the serum levels of isoniazid (INH), rifampicin (RFP), and pyrazinamide (PZA), three antibiotics used in patients with spinal tuberculosis using capillary electrophoresis (CE). A standard solution of INH, RFP, and PZA was prepared and mixed with serum to prepare the standard curve. The detection limit, quantification limit, precision, stability, repeatability, and sample recovery were determined. Then, INH, RFP, and PZA were measured from the leftover serum samples of all patients with spinal tuberculosis who were treated with 2SHRZ/2.5H2R2Z2 combined with surgery in a tertiary hospital in Qinghai from October 2015 to September 2017. A total of 107 patients with spinal tuberculosis treated using the 2SHRZ/2.5H2R2Z2 regimen combined with surgery were included in this study. All three antibiotics had linear standard curves with high correlation coefficients ( R 2 = 0.9997, 0.9994, and 0.9986). The recovery rates were 98.1% for INH, 96.5% for PZA, and 97.2% for RFP. The results from the serum samples showed that the plasma concentrations of INH (4.989 ± 1.692 μg mL −1 ) and RFP (9.400 ± 1.711 μg mL −1 ) reached effective therapeutic concentrations in all patients, but not PZA (33.860 ± 1.830 μg mL −1 ). The CE method for measuring INH, RFP, and PZA simultaneously in serum samples of patients with spinal tuberculosis is simple, rapid, and sensitive. This method is suitable for the routine monitoring of INH, RFP, and PZA concentrations in the serum of patients with spinal tuberculosis.